Implementasi Bimbingan Belajar Membaca Menulis Berhitung Kelas III Madrasah Ibtidaiyah Darurrohman Kertanegara Haurgeulis - Salmiah; Abdur Rahim (Jurnal Penelitian Multidisiplin Ilmu, 2022)
In everyday life, especially at school, reading, writing and arithmetic are the foundation or basis in learning, so that students can understand learning well. If students cannot read, write and count well, then students cannot follow learning to a higher level, because reading, writing and arithmetic is the basis for someone to receive learning material. This study aims to determine the implementation of tutoring for students who have difficulty learning to read, write, and count in class III Madrasah Ibtidaiyah Darurrohman Kertanegara Haurgeulis and to describe and explain the factors supporting and inhibiting the implementation of tutoring for class III students of Madrasah Ibtidaiyah Darurrohman Kertanegara Haurgeulis. The research method used in this study is a qualitative research method. Data collection techniques used are interviews, observation, and documentation. The subjects in this study were third grade students of MI Darurrohman Kertanegara Haurgeulis. The results of field research on the implementation of tutoring for reading, writing and arithmetic in class III Madrasah Ibtidaiyah Darurrohman Kertanegara Haurgeulis showed that: (1) The implementation of tutoring for reading, writing, and arithmetic in class III Madrasah Ibtidaiyah Darurrohman Kertanegara had been implemented well but not yet appropriate. With the concept of proper tutoring. In the implementation of tutoring the teacher uses the method of improvement and enrichment; (2) The supporting factors for the implementation of tutoring for class III students of Madrasah Ibtidaiyah Darurrohman Kertanegara Haurgeulis are the preparation of facilities and infrastructure as well as the volunteerism of homeroom teachers and guidance teachers to provide guidance, while the inhibiting factors for the implementation of tutoring are the lack of student motivation and support from family/parents.